DNA aptamer selected for specific recognition of prostate cancer cells and clinical tissues - Huang, Zhi-Xiang; Xie, Qin; Guo, Qiu-Ping; Wang, Ke-Min; Meng, Xiang-Xian; Yuan, Bao-Yin; Wan, Jun; Chen, Yuan-Yuan (Chinese chemical letters, 2017)
Prostate cancer is the most common malignancy in men lack of efficient early diagnosis and therapeutics,calling for effective molecular probes.Herein,we performed cell-based systematic evolution of ligands by exponential enrichment（cell-SELEX） to obtain specific recognition of human prostate cancer cells PC-3M.Four aptamers were successfully obtained that can bind to target cells with high affinity and specificity.A 51-nt truncated sequence named Xq-2-C1 was identified after further elaborative analysis on the secondary structure.More importantly,the achieved aptamer Xq-2-C1 not only demonstrated excellent specific to target cells,but also revealed specific recognition to clinical prostate cancer tissue.The tissue imaging results showed that Xq-2-C1 had better recognition ratio for clinical prostate cancer tissue samples（85%） compared to the random sequence（9%）.These results demonstrate that these newly generated aptamers would furnish potential applications in the early diagnosis and clinical treatment of prostate cancer.